Pengembangan dan Pengoptimalan Pemanfaatan Tanaman Odot sebagai Pakan Hijauan Unggul pada Kelompok Tani Cendana Koto XI Tarusan Kabupaten Pesisir Selatan - Tinda Afriani; Khasrad; Dian Hafizah; Ade Fadhilah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Odot plants have significant potential to enhance livestock productivity and agricultural sustainability. This extension aims to increase farmers' knowledge about the benefits of Odot plants and its cultivation techniques. The extension method involves forming a service team and meeting with farmer groups. The extension program includes information on the benefits of Odot plants, cultivation techniques, maintenance, and harvesting. Practical field training was also provided to farmers. The extension results showed a positive response from farmers, who actively participated in the extension activities. They understood the potential of Odot plants in improving livestock productivity. These plants are nutrient-rich and can be used as a high-quality feed source. Importantly, using Odot as supplementary livestock feed has a high potential to support healthy and efficient livestock production, giving farmers confidence in their livestock management. This extension is a crucial step in promoting sustainable agriculture and livestock farming.